2014
DOI: 10.1093/heapol/czu125
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of chronic conditions among households in Myanmar: the case of angina and asthma

Abstract: Myanmar is expanding public spending on health and has recently launched an innovative programme for supporting hospital-based care for poor households. Our findings suggest the need for interventions to address OOP expenses associated with outpatient care (including drugs) for chronic conditions in Myanmar's population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Recent studies have compared PSM and coarsened exact matching, a newer method that uses stratification followed by exact matching of cohorts for key variables influencing study endpoints with strata-based weighting according to the proportion of patients in each stratum 12,3133. The matching methods produced similar results in these studies; however, Wells et al12 reported that coarsened exact matching retained more patients and achieved better balance between cohorts than PSM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have compared PSM and coarsened exact matching, a newer method that uses stratification followed by exact matching of cohorts for key variables influencing study endpoints with strata-based weighting according to the proportion of patients in each stratum 12,3133. The matching methods produced similar results in these studies; however, Wells et al12 reported that coarsened exact matching retained more patients and achieved better balance between cohorts than PSM.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the sample was projected from 2008 to 2012, applying the weights of situations of dependence by level and autonomous community, and considering the 2012 population data. Hence, the results should not be greatly affected by this lag in the data sources, since the evolution in the prevalence of disability tends to remain unchanged over time [48]. For instance, in Spain the prevalence of disability amounted to 6.2% in 1999 and 6.5% in 2008, while that of long term care increased only from 4.4% to 5.1% in the same time period [96].…”
Section: Discussionmentioning
confidence: 99%
“…However, those analyzing the effects of OPP payments or health insurance on LTC are more limited in number although interest in this issue is growing. Some studies have analyzed OOP payments for specific components of health care such as the chronically ill [47,48] and the disabled population [49][50][51]. In addition, a study across the OECD has measured the protection of long-term care and differences between countries.…”
mentioning
confidence: 99%
“…However, those analyzing the effects of OPP payments or health insurance on LTC are more limited in number although interest in this issue is growing. Some studies have analyzed OOP payments for specific components of health care such as the chronically ill [34,35] and the disabled population [36][37][38]. In addition, a study across the OECD has measured the protection of long-term care and differences between countries.…”
Section: Documented In the Case Of Private Health Insurance Systemsmentioning
confidence: 99%